Synthesis, characterization, and cytotoxicity of iron oxide nanoparticles - Kanagesan, Samikannu; Hashim, Mansor; Subramani, Tamilselvan; Mohammed Alitheen, Noorjahan Banu; Ismail, Ismayadi; Hajalilou, Abdollah; Kaiser, Ahsanul (Hindawi Publishing Corporation, 2013)
In order to study the response of human breast cancer cells' exposure to nanoparticle, iron oxide (α-Fe2O3) nanoparticles were synthesized by a simple low temperature combustion method using Fe(NO3)3·9H2O as raw material. X-ray diffraction studies confirmed that the resultant powders are pure α-Fe2O3. Transmission electron microscopy study revealed the spherical shape of the primary particles, and the size of the iron oxide nanoparticles is in the range of 19 nm. The magnetic hysteresis loops demonstrated that the sample exposed ferromagnetic behaviors with a relatively low coercivity. The cytotoxicity of α-Fe2O3 nanoparticle was also evaluated on human breast cancer cells to address the current deficient knowledge of cellular response to nanoparticle exposure.